Clinical potential of implantable wireless sensors for orthopedic treatments. (3rd April 2018) - Karipott, Salil Sidharthan; Nelson, Bradley D.; Guldberg, Robert E.; Ong, Keat Ghee
ABSTRACT: Introduction : Implantable wireless sensors have been used for real-time monitoring of chemicals and physical conditions of bones, tendons and muscles to diagnose and study orthopedic diseases and injuries. Due to the importance of these sensors in orthopedic care, a critical review, which not only analyzes the underlying technologies but also their clinical implementations and challenges, will provide a landscape view on their current state and their future clinical role. Areas covered : By conducting an extensive literature search and following the leaders of orthopedic implantable wireless sensors, this review covers the battery-powered and battery-free wireless implantable sensor technologies, and describes their implementation for hips, knees, spine, and shoulder stress/strain monitoring. Their advantages, limitations, and clinical challenges are also described. Expert commentary : Currently, implantable wireless sensors are mostly limited for scientific investigations and demonstrative experiments. Although rapid advancement in sensors and wireless technologies will push the reliability and practicality of these sensors for clinical realization, regulatory constraints and financial viability in medical device industry may curtail their continuous adoption for clinical orthopedic applications. In the next five years, these sensors are expected to gain increased interest from researchers, but wide clinical adoption is still unlikely.